The Spatial Arrangement of The Electric Field in the Needle-Plate Electrospinning - Ahmad Kusumaatmaja; Muhamad Nasrudin Manaf; Shiddiq Nur Hidayat; Kuwat Triyana; Farah Rahma; Grandprix T. M. Kadja; Muchammad Yunus (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2023)
The electric field distribution of the Neddle-Plate (NP) electrospinning set up has reported due to the simple classical electrodynamics solutions. The charge is assumed to distribute uniformly in the needle (nozzle) and the collector (plate). The electric field has an influence only in the early stage of the electrospinning process. The electric field and the viscosity of the jet fluid have caused the bending of the straight jet. The high viscosity of the fluid can preserve the straight jet length much longer. The electric field gives the initial angular momentum of the jet due to the whipping motion of the jet. For the area away from the nozzle, the electric does not influence the whipping motion. Then the whipping motion solely due to the influence from the charge repulsion of the jet fluid and the evaporation of the solvent.